2014
DOI: 10.1002/cctc.201301090
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Enzymatic Halogenation of Substituted Tryptophan Derivatives using the FAD‐Dependent Halogenase RebH

Abstract: Regioselective methods to establish carbon–halide bonds are still rare, although halogenation is considered as a commonly used methodology for the functionalization of organic compounds. The incorporation of halogen substituents by organic synthesis usually requires hazardous conditions, shows poor regioselectivity and results in the formation of unwanted byproducts. In addition, halogenation by electrophilic aromatic substitution (SEAr) obeys distinct rules depending on electron‐withdrawing or ‐donating group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 29 publications
2
99
0
9
Order By: Relevance
“…Top: In vivo formation of chlorinated pacidamycin by the chlorination of tryptophan (2)t oform 7-chlorotryptophan by the flavin-dependent tryptophan halogenase PrnA prior to incorporation into pacidamycin biosynthesis. [85] Shepherd et al extended the biocatalytic scope of PrnA and PyrH even further by not only using substituted tryptophans,b ut also aniline derivatives,s uch as anthranilic acid and kynurenine (Figure 3), thereby showing that the substrate specificity of tryptophan halogenases is clearly not as high as originally assumed and that their substrate scope is not restricted to indole derivatives. [77,78,80] they are very sensitive to oxygen.…”
Section: Production Of Halogenated Compounds In Vitromentioning
confidence: 93%
See 1 more Smart Citation
“…Top: In vivo formation of chlorinated pacidamycin by the chlorination of tryptophan (2)t oform 7-chlorotryptophan by the flavin-dependent tryptophan halogenase PrnA prior to incorporation into pacidamycin biosynthesis. [85] Shepherd et al extended the biocatalytic scope of PrnA and PyrH even further by not only using substituted tryptophans,b ut also aniline derivatives,s uch as anthranilic acid and kynurenine (Figure 3), thereby showing that the substrate specificity of tryptophan halogenases is clearly not as high as originally assumed and that their substrate scope is not restricted to indole derivatives. [77,78,80] they are very sensitive to oxygen.…”
Section: Production Of Halogenated Compounds In Vitromentioning
confidence: 93%
“…They catalyze highly selective and specific halogenation reactions without the formation of any byproducts except water, and in the case of flavin-dependent halogenases,h ydrogen peroxide,f ormed by the reaction of FADH 2 with oxygen. [73,[83][84][85][86] Lang et al showed in 2011 that the regioselectivity of halogenases can be modified by site-directed mutagenesis.W hen al arge phenylalanine residue close to the bound substrate tryptophan in the tryptophan 7-halogenase PrnA was exchanged against asmall alanine residue,the regioselectivity of PrnA was affected and PrnA showed additional tryptophan 5-halogenase activity. Fluorinase has extremely high substrate specificity and so far S-adenosyl-lmethionine is the only known substrate of this enzyme and of the related chlorinase.H owever, fluorinase can be used to produce 18 F-labeled molecules for use in diagnostics.…”
Section: Production Of Halogenated Compounds In Vitromentioning
confidence: 99%
“…[12] In contrast to previous reports for another FDH, PrnA, [13] RebH was found to halogenate many of these substrates at sites other than those most electronically activated, providing regioselectivity that would not be obtained from conventional EAS. The unnatural substrates halogenated by RebH in both our [12] and others’ [14] work were, however, comparable in size to the native substrate, tryptophan ( 1 , Scheme 1), and increasing structural differences led to lower turnover numbers and less favorable kinetic parameters. [12] Given a recent report in which cross-linked RebH aggregates were used for gram scale halogenation, [15] the narrow substrate scope and low activity of RebH on unnatural substrates stand as key limitations to its general utility for preparative halogenation.…”
mentioning
confidence: 91%
“…Thus far, most of this work has been focussed on the tryptophan halogenases and has revealed a number of enzymes capable of halogenating tryptophan derivatives, 218 non-natural indolic substrates, 150,155,[219][220][221] in addition to benzamides and benzoic acids 150,155 as well as napthols and napthyl amines (Figure 19). 220,221 In a number of cases, halogenation occurs with good regioselectivity.…”
Section: Substrate Scope Of Fl-halsmentioning
confidence: 99%
“…[32][33][34]218,224,225 This is likely to be an artefact of these enzymes evolving as part of the biosynthetic pathways to non-essential secondary metabolites. Halogenases are not essential for the survival or growth of the native host, and hence there has been little evolutionary pressure for highly active halogenase enzymes.…”
Section: Engineering Fl-hals To Improve Activity and Stabilitymentioning
confidence: 99%